1998
DOI: 10.1021/ja981123a
|View full text |Cite
|
Sign up to set email alerts
|

O2 Activation and Aromatic Hydroxylation Performed by Diiron Complexes

Abstract: Chemical models of active sites of diiron oxo proteins have been synthesized. The polydendate ligands are EDTA derivatives which provide a balanced supply of nitrogen atoms and carboxylate groups together with an oxidizable phenyl moiety, thus mimicking both the iron coordination in methane monooxygenase and a nearby substrate site. All the diferric complexes have been characterized in solution by ESI-MS, optical absorption, and in some cases by 1H NMR. In the case of the ligand L1 [L1 = (N,N‘-bis(3,4,5-trimet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
59
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 81 publications
(64 citation statements)
references
References 62 publications
4
59
1
Order By: Relevance
“…However, a surprising observation was made by Fontecave -three-carbon-chained EDTA derivatives had a very poor affinity towards iron(III). [76] Therefore, more bulky, hydrophobic systems are used, maintaining the two-carbon alkyl chains disabling water interaction in the first coordination sphere. This reflects the relaxivity of the CAs, so the most attractive approach to achieving high r 1 values as allowed in the case of gadolinium(III) complexes is not accepted in that of iron.…”
Section: How To Mute Catalytic or Redox Activity On The Metalmentioning
confidence: 99%
“…However, a surprising observation was made by Fontecave -three-carbon-chained EDTA derivatives had a very poor affinity towards iron(III). [76] Therefore, more bulky, hydrophobic systems are used, maintaining the two-carbon alkyl chains disabling water interaction in the first coordination sphere. This reflects the relaxivity of the CAs, so the most attractive approach to achieving high r 1 values as allowed in the case of gadolinium(III) complexes is not accepted in that of iron.…”
Section: How To Mute Catalytic or Redox Activity On The Metalmentioning
confidence: 99%
“…O incorporation was observed. [58] The authors thus showed, that the incorporated oxygen atoms exclusively arose from the added oxidizing reagent, not from the bridging oxido ligand. On the basis of todays knowledge this experiment permits a further conclusion: A high-valent diiron(IV) species with a terminal oxido ligand is most likely not the oxidizing species.…”
Section: Treatment Of [(Mben) 2 Fe 2 a C H T U N G T R E N N U N G (Mmentioning
confidence: 99%
“…Complexes 1 and 2 exhibit similar reactivity patterns, but 1 generates a more powerful oxidant than 2. Recently, efficient and selective intramolecular aromatic hydroxylations were reported with mononuclear [28,29] or dinuclear [30][31][32][33][34] iron complexes in which the aromatic ring is forced into close proximity of the iron center by a covalent linkage to the supporting polydentate ligand. The need to independently prepare the compounds containing both reactive iron center and the aromatic substrate, however, limits the applicability of these systems.…”
Section: Introductionmentioning
confidence: 99%